Developing escape strategies for copepods using Q-learning - Holmberg, Erik (My University, 2019)
Copepods are a type of small crustaceans with the ability to move using powerful jumps. This project seeks to develop a model for the dynamics of these copepods in the turbulent flows of the oceans and then apply Q-learning to find good navigation strategies. Contained in this project is also the development of a statistical model of a turbulent flow. It is found that using Q-learning it is possible for the simulated copepods to learn strategies that allow them to avoid dangerous areas almost equally as well as more simple strategies that require more information.
Keywords: Machine learning; Fluid mechanics; Simulation; Copepods; Q-learning